D’un regard… à l’autre - Mendelsohn, Sophie; Wallet, Krystel (Ciel variable, 2004)
Abstract During a stay in Paris, Sorel Cohen set up her camera in different psychoanalysts' offices. The result was a series of images around the analyst's couch, the body that we must divine by its very absence, and the challenge of showing the unshowable, of capturing a site of intimacy in a flickering that leaves it to its finishing, or its famishing ... for if the desire is there - the desire to see, to know - it must constandy be reawoken. One work, in fact, is called Désir, désir, désir: in it, might we hear the quiet music of the artist, who for many years photographed around beds before falling upon couches?